2020
DOI: 10.3389/fneur.2020.00490
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evidence Regarding the Association Between Migraine and Suicidal Behaviors: A Systematic Review

Abstract: Objective: The review presents a systematic analysis of literature investigating the association between migraine and suicidal behaviors. Introduction: Migraine is a common neurological disorder. The prevalence of migraines increases with age from adolescence to adulthood in both sexes, and results in a substantial loss of productivity due to missing days of school or work and need for bed rest. Literature prior to 2015 suggests that migraine is a predictor of suicide. Given the worldwide public health interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Migraine has also been shown to lead to an increased risk of suicidal behaviors, in both the clinical and general population, and among chronic migraineurs with and without aura ( 185 , 186 ). The research with low bias ratings overwhelmingly supports a strong relationship between migraine and suicidal behaviors ( 34 , 185 ).…”
Section: Psychological Risk Factors and Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine has also been shown to lead to an increased risk of suicidal behaviors, in both the clinical and general population, and among chronic migraineurs with and without aura ( 185 , 186 ). The research with low bias ratings overwhelmingly supports a strong relationship between migraine and suicidal behaviors ( 34 , 185 ).…”
Section: Psychological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…Migraine has also been shown to lead to an increased risk of suicidal behaviors, in both the clinical and general population, and among chronic migraineurs with and without aura ( 185 , 186 ). The research with low bias ratings overwhelmingly supports a strong relationship between migraine and suicidal behaviors ( 34 , 185 ). The role of depression in this relationship is unquestionable, with a clear bidirectional relationship between depression or anxiety disorders and migraines, which can increase the risk of suicide ( 34 , 88 ).…”
Section: Psychological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…In other words, an effective suicide prevention programme is organised to complement the regional welfare and social safety nets that lead to an improvement in the vulnerability of regional social protection against suicidal behaviour/ideation via effective leading/exposure procedures, such as the regional intervention model programme. It is well known that patients with chronic physical disease, such as cancer [ 48 ], and chronic diseases, such as atopic dermatitis [ 49 ], asthma [ 50 ], migraine [ 51 ] and end-stage kidney disease treated with dialysis [ 52 ], are at a high risk of suicide and comorbidities with affective disturbance. Therefore, suicide mortality caused by physical illness-related motives could probably be prevented by the external cooperation of regional primary care physicians and psychiatry specialists, via suicide prevention programmes, due to the guidance to help them access appropriate services.…”
Section: Discussionmentioning
confidence: 99%
“…Severity related to QOL, and the development of other actions can be a singular metric or a combination. Some research has reported that migraine with aura is a more accurate predictor of increased risk of self-harm or suicide, while other studies have determined that the presence of aura is not required [24,25]. One explanation for this dichotomy may be that migraine symptoms are multi-factorial and diverse, so one metric alone is unlikely to be a significant predictor.…”
Section: Introductionmentioning
confidence: 99%